2007
DOI: 10.1111/j.1745-7254.2007.00500.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of inflammation-related genes of polysaccharides fractionated from mycelia of medicinal basidiomycete Antrodia camphorata

Abstract: Aim: To investigate the effect of water soluble‐ethanol precipitation fraction (AC‐1) and alkaline extraction‐isoelectric precipitation fraction (AC‐2) from Antrodia camphorata (Polyporaceae, Aphyllophorales) on lipopolysaccharide (LPS)‐induced gene activation in mouse macrophages. Methods: The AC‐1 and AC‐2 fractions were prepared, and their effects on LPS‐induced gene expression were monitored by Western blotting and RT‐PCR. Results: Our results indicated that AC‐2, but not AC‐1 dose‐dependently (50–200 mg/L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 46 publications
4
24
0
Order By: Relevance
“…These antioxidant results are consistent with previous studies, 33,34) in which it was reported that polysaccharides from water extracts of submerged culture mycelia (similar to our preparation of AC-PS) displayed better antioxidant capabilities than extracts of non-submerged culture mycelia or dry matter from the culture medium. 21,35) Therefore, although in the present study AC-PS did not show any significant anti-tumor effects as AC-FB and AC-SS did, it might have better anti-inflammatory and anti-oxidant effects than AC-FB or AC-SS.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These antioxidant results are consistent with previous studies, 33,34) in which it was reported that polysaccharides from water extracts of submerged culture mycelia (similar to our preparation of AC-PS) displayed better antioxidant capabilities than extracts of non-submerged culture mycelia or dry matter from the culture medium. 21,35) Therefore, although in the present study AC-PS did not show any significant anti-tumor effects as AC-FB and AC-SS did, it might have better anti-inflammatory and anti-oxidant effects than AC-FB or AC-SS.…”
Section: Discussionsupporting
confidence: 82%
“…26,27) The Mw of AC-PS was much higher (400 to above 20,000 Da) than that of AC-FB or AC-SS, suggesting that the AC-PS, which are water extracts of cultured mycelium, had different polysaccharide fractions than other preparations. [28][29][30] In addition, we found that AC-PS contained the largest amounts of polysaccharides of all the A. camphorata extracts (AC-PS, 29.5 mg/mL versus 0.1, 0.2, 5.9 for AC-FB, AC-SS and AC-LS respectively).…”
Section: Discussionmentioning
confidence: 99%
“…These results demonstrated that lignin removal rendered xylan more accessible to xylanase, which in turn rendered cellulose more accessible to cellulase, as noted previously (Kumar and Wyman 2009). Interestingly, the brown-rot fungus Antrodia wangii Cui 7568 did not remove lignin but interfered with lignocellulose decaying to polysaccharides (Wu et al 2007). It also contributed to cellulose and hemicellulose conversion, demonstrating that delignification was not the only way to accelerate conversion rates.…”
Section: Influence Of Lignin Removal On Cellulose Conversion and Hemisupporting
confidence: 67%
“…The fungus is native to Taiwan, where it grows in the walls of the inner heartwood of Cinnamomum kanehirai Hay (Chang and Chou 1995;Wu et al 1997), and has been ascribed various medicinal properties Wu et al 2007). Our research has also revealed that submerged cultures of A. camphorata are highly odiferous, suggesting that the mushroom might serve as an important source of natural aroma compounds for the food and cosmetic industries.…”
Section: Introductionmentioning
confidence: 83%